Intravenous immunoglobulins in dermatology. Part 2: clinical indications and outcomes. (17th May 2018) - Forbat, E.; Ali, F. R.; Al‐Niaimi, F.
Summary: Intravenous immunoglobulin (IVIg) is a solution of human IgG, salt, sugars and solvents used to treat a multitude of diseases. Although IVIg has been known to treat many diseases safely and successfully, there are relatively few supporting randomized controlled trials. In part two of this review, we assess the clinical indications of IVIg in dermatological disorders and the outcomes of its use. Abstract : Clickhere for the corresponding questions to this CME article.